Karakteristik Kalus dari Eksplan Batang Planlet Krisan (Chrysanthemum morifolium Ramat) pada Media dengan Konsentrasi 2,4-Dichlorophenoxyacetic Acid (2,4-D) dan 6-Benzylaminopurine (BAP) serta Kondisi Pencahayaan - Tia Setiawati; Annisa Nur Arofah; Ani Lestari; Rusdi Hasan (Pro-Life, 2024)
This research aimed to obtain the optimal concentration combination of 2,4-D and BAP growth regulators for inducing callus from the stem explant of Chrysanthemum (C. morifolium Ramat) in bright and dark conditions. Stem explants of chrysanthemum were grown in culture medium supplemented with various concentrations and combinations of 2,4-D and BAP under different lighting conditions for 45 days after culture. A laboratory-scale experimental method was used in this research using Completely Randomized Design (CRD). The observed parameters were induction time, percentage formation, size, fresh weight, dry weight, texture, color, and various respones generated by callus. All data were analyzed descriptively. The results showed that all concentrations and combinations of growth regulators could induce callus. In bright condition, the fastest callus induction time was 7 days after culture; most calli were dark green and dark brown colored with compact texture; the callus size was 1.36 cm; also, the highest dry weight generated by callus was 0.17 gram. Meanwhile, in dark conditions, the fastest callus induction time was 6 days after culture; most calli were light green and light brown colored with compact texture; the callus size was 1.18 cm; and the highest dry weight generated by callus was 0.15 gram.